PENINGKATAN KOMPETENSI GURU SMA AL-FURQAN JEMBER MELALUI WORKSHOP DEEP LEARNING BERBANTUAN AI - Randi Pratama Murtikusuma; Ervin Oktavianingtyas; Dinawati Trapsilasiwi; Robiatul Adawiyah (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital transformation in education requires teachers not only to master technology but also to integrate it into meaningful learning practices. This community service program aimed to enhance the competencies of teachers at SMA Al-Furqan Jember in implementing deep learning supported by artificial intelligence (AI). The activity was conducted through an intensive workshop involving 16 teachers from various subject areas, focusing on strengthening AI literacy, understanding the concepts of deep learning namely meaningful, mindful, and joyful learning and utilizing Padlet TA and Gimkit as learning platforms. The implementation methods included needs analysis, theoretical and practical training sessions, as well as evaluation through pre-tests, post-tests, questionnaires, and interviews. The results showed an improvement in teachers’ competencies in designing AI-assisted lesson plans, developing interactive learning activities, and understanding deep learning concepts more comprehensively. Teachers also expressed positive responses to the use of Padlet and Gimkit, as these tools were considered effective in increasing student engagement and learning creativity. This program demonstrates that practice-based mentoring is effective in supporting the sustainable implementation of deep learning in school-based instruction. ABSTRAK Transformasi digital dalam pendidikan menuntut guru tidak hanya menguasai teknologi, tetapi juga mampu mengintegrasikannya dalam pembelajaran yang bermakna. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kompetensi guru SMA Al-Furqan Jember dalam menerapkan pembelajaran deep learning berbantuan kecerdasan buatan (AI). Kegiatan dilaksanakan melalui workshop intensif yang melibatkan 16 guru dari berbagai mata pelajaran, dengan fokus pada penguatan literasi AI, pemahaman konsep deep learning yang meliputi meaningful, mindful, dan joyful learning, serta pemanfaatan platform Padlet TA dan Gimkit. Metode pelaksanaan meliputi analisis kebutuhan, pelatihan teori dan praktik, serta evaluasi melalui pre-test, post-test, angket, dan wawancara. Hasil kegiatan menunjukkan adanya peningkatan kompetensi guru dalam menyusun perangkat pembelajaran berbantuan AI, merancang aktivitas pembelajaran interaktif, serta memahami konsep pembelajaran mendalam secara lebih komprehensif. Guru juga memberikan respons positif terhadap penggunaan Padlet dan Gimkit karena dinilai mampu meningkatkan keterlibatan dan kreativitas dalam pembelajaran. Kegiatan ini membuktikan bahwa pendampingan berbasis praktik efektif dalam mendorong implementasi pembelajaran deep learning secara berkelanjutan di sekolah.